Structural performance and sustainability assessment of hybrid-cold formed modular steel frame. (February 2021) - N.Usefi; Sharafi, P.; Mortazavi, M.; Ronagh, H.; Samali, B.
Abstract: Hybrid cold-formed steel (HCFS) structures are new structural systems in the light steel construction industry offering new possibilities, in particular with regard to the applications in mid-rise construction. The structural performance, sustainability as well as the economic and social costs of these structures are of great importance for decision-makers when it comes to deciding on employing these systems and comparing them with their conventional counterparts. In this study, the HCFS systems are evaluated with respect to sustainability, structural performance, economic cost, and social impacts. The results then are compared with those of Ordinary Moment Resisting Frames (OMRF), as the most popular conventional HRS framed system. The methodology consists of both qualitative and quantitative analyses that include the overview of the positive and negative points of each construction method in the form of a comparative study. The results of the structural analysis of the two construction systems show that the hybrid system exhibits better structural performance with regard to the storey shear and drift. It is also shown that in terms of most environmental performance indicators, HCFS framed structures can lead to less environmental impact than OMRF systems. Moreover, the economic assessment demonstrates that HCFS framed structures can save up to the 23% in framing costs, compared to OMRF systems, primarily owing to the fact that lightweight flooring system can be easily incorporated to the design of HCFS structure. Their great potential for prefabrication, on the other hand, makes HCFS a better option with respect to many social compact indicators such as noise, air, vibration and dust pollution and traffic. Highlights: Study of Hybrid cold formed-hot rolled steel (CFS-HRS) frames in building construction. Assessment of structural performance and a comparison with Ordinary Moment Resisting Framed (OMRF) systems. Assessment of sustainability indexes and environmental impacts and a comparison with OMRF systems. Social impact assessment of construction and a comparison with OMRF systems.